Assessment of Nepalese Electricity Security Scenario after an Unusual Downpour - Dahal, Swaechchha; Sharma, Aliya; Chhetri, Bhupendra Bimal (Journal of Science and Engineering, 2025)
Climate change induced extreme weather events have been disrupting the services of electricity infrastructure worldwide. Nepal is one of the highly vulnerable countries to climate change due to its terrain diversity, weak geology, and unpredictable seasonal rainfall patterns. Frequent floods, landslides, and prolonged dry periods, during very cold to extreme hot seasons, are causing serious challenges to the power system operation in Nepal. This study, therefore, attempts to discuss the impacts of an unusual heavy downpour on the Nepalese power system. It focuses on the short-term and medium-term impact of the extreme weather event on generation capacity, resulting in increased interruptions and imports, which clearly indicates a low electricity supply security situation. Such an event in September 2024 caused almost 1/3 of the generation capacity loss. The effect was more pronounced in the dry period energy balance that followed the event. Therefore, the authors discuss this issue in a broader context, considering Nepal’s geography and future electricity generation mix. Specific considerations of geographical diversity in generation and transmission infrastructure reinforcement and expansion are recommended. The need for cohesive partnerships, data-driven, crisis-ready electricity supply management, and wider stakeholder engagement in ascertaining electricity security is emphasized.